Thrombospondin-2 as a Biomarker of Advanced Liver Fibrosis in Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD) - Budyono, Catarina; Ahda, Fatikha Rudia (The Indonesian Society for Digestive Endoscopy, 2025)
Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD) is a highly prevalent liver disorder associated with obesity and metabolic syndrome, replacing the term Non-Alcoholic Fatty Liver Disease (NAFLD). The diagnosis of MAFLD is established based on the presence of hepatic steatosis accompanied by metabolic abnormalities such as overweight/obesity, type 2 diabetes mellitus, or metabolic dysregulation. Although liver biopsy remains the gold standard for diagnosis, its invasive nature underscores the need for practical, non-invasive biomarkers. This review aims to summarize the current evidence regarding thrombospondin-2 (TSP-2) as a potential biomarker of hepatic fibrosis in MAFLD. Recent data indicate that serum TSP-2 levels correlate with the severity of steatosis, inflammation, and fibrosis. TSP-2 also shows promise in distinguishing simple steatosis from steatohepatitis and in identifying patients at risk of advanced fibrosis. While these findings highlight the potential role of TSP-2 in diagnosis and disease monitoring, further clinical validation is required before its routine implementation in clinical practice.